Space charge analysis for low energy photoinjector. Issue 1 (1st January 2023) - Carillo, M; Behtouei, M; Bosco, F; Faillace, L; Ficcadenti, L; Fukasaway, A; Giuliano, L; Mostacci, A; Migliorati, M; Spataro, B; Rosenzweig, J; Palumbo, L
Abstract: Beam dynamics studies are performed in the context of a C-Band hybrid photo-injector project developed by a collaboration between UCLA/Sapienza/INFN-LNF/RadiaBeam [1, 2]. These studies aim to explain beam behaviour through the beam-slice evolution, using analytical and numerical approaches. An understanding of the emittance oscillations is obtained starting from the slice analysis, which allows correlation of the position of the emittance minima with the slope of the slices in the transverse phase space (TPS). At the end, a significant reduction in the normalized emittance is obtained by varying the transverse shape of the beam while assuming a longitudinal Gaussian distribution. Indeed, the emittance growth due to nonlinear space-charge fields has been found to occur immediately after moment of the beam emission from the cathode, giving insight into the optimum laser profile needed for minimizing the emittance.